Catenin signaling controls phrenic motor neuron development and function during a narrow temporal window - Vagnozzi, Alicia N.; Moore, Matthew T.; López de Boer, Raquel; Agarwal, Aambar; Zampieri, Niccolò; Landmesser, Lynn T.; Philippidou, Polyxeni (Frontiers in Neural Circuits, 2023)
Phrenic Motor Column (PMC) neurons are a specialized subset of motor neurons (MNs) that provide the only motor innervation to the diaphragm muscle and are therefore essential for survival. Despite their critical role, the mechanisms that control phrenic MN development and function are not well understood. Here, we show that catenin-mediated cadherin adhesive function is required for multiple aspects of phrenic MN development. Deletion of β- and γ-catenin from MN progenitors results in perinatal lethality and a severe reduction in phrenic MN bursting activity. In the absence of catenin signaling, phrenic MN topography is eroded, MN clustering is lost and phrenic axons and dendrites fail to grow appropriately. Despite the essential requirement for catenins in early phrenic MN development, they appear to be dispensable for phrenic MN maintenance, as catenin deletion from postmitotic MNs does not impact phrenic MN topography or function. Our data reveal a fundamental role for catenins in PMC development and suggest that distinct mechanisms are likely to control PMC maintenance.